Lecturers’ Knowledge and Skill in the Integration of Information and Communication Technology into Business Education Instruction in Nigerian Colleges of Education - Olaniyi, Laidi Hakeem (West African Journal of Open and Flexible Learning, 2015)
The lecturers' roles are to facilitate learning and help students to develop into autonomous learners who can continue to learn by themselves, especially with the assistance of new ICT. There is however, definite deficit in the knowledge and skill needed for the use of ICT as an effective teaching learning tool among lecturers. Lecturers need to understand how to incorporate ICT into their lessons; hence they may need to develop pedagogies to achieve this competency. This paper aimed at surveying lecturers' knowledge and skill in the integration of ICT pedagogy into Business Education instruction in Nigerian colleges of education. The study also aimed at determining the level of ICT knowledge of Business Education lecturers in their ICT integration pedagogy in colleges of education. It also, ascertained whether the lecturers' skill of ICT tools influence ICT integrated pedagogy in the colleges of education. The population comprises all Business Education lecturers in the colleges of education in South West geo political zone of Nigeria. A census of lecturers in four purposively selected colleges of education was taken because there is availability of ICT unit in the colleges. A total of 37 lecturers (23 males and 14 females) across four colleges of education were taken as research sample and questionnaire were administered to the sample respondents across the colleges simultaneously. The study was guided by two research questions and two hypotheses were formulated. Data collected on the study were analysed using simple percentage, t-test and ANOVA statistical tools. The paper recommends that Business Education lecturers should be encouraged to improve on their pedagogical practices; modelling the use of ICT they teach in their pedagogical practices; and shift away from lecture to activity oriented teaching learning approach.
Keywords: Technological Pedagogical Content Knowledge (TPACK); Information and Communication Technologies (ICT); business education lecturers; knowledge and skill